A framework for electronic services system. (17th July 2008) - Sandhu, Kamaljeet; Corbitt, Brian
This paper reports on developing a framework for web-based EServices Acceptance Model (E-SAM). The paper argues that User Experience, User Motivation, Perceived Usefulness (PU), Perceived Ease of Use (PEOU) may influence User Acceptance of web-based Eservices. The model was examined at a university where students and staff use services that have moved from a paper-based to web-based EService system. The findings from the data analysis suggest that User Experience is strongly related to PEOU; and PU to User Motivation in User Acceptance of Web-based Eservices. The bonding of these variables and the lack of strong relationships between other components suggest that the model's application to Eservices and highlight a research framework.